ЦЕННОСТИ И АНТИЦЕННОСТИ В СОВРЕМЕННЫХ БРИТАНСКИХ И АВАРСКИХ РАССКАЗАХ / VALUES AND DISVALUES IN MODERN BRITISH AND AVAR STORIES / VALORI ŞI NON-VALORI ÎN POVESTIRILE MODERNE BRITANICE ŞI AVARE - Haibat Kadachieva (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2013)
The article highlights linguocultural peculiarities of contemporary British and Avar ethnicities. The comparative study of nuclear and periphery values contribute to creation and interpretation of universal/ specific features of the given mentalities and their worldviews.